On the lower bound of spectrum of the Schrödinger’s operator for some multi-particle systems - Khalmukhamedov, O. R. (Institute for Mathematical Research (INSPEM), Universiti Putra Malaysia, 2016)
For N - particle Schrödinger’s operator with Column potential with central charge equal Z, it is well known estimation N < 2Z +1, obtained by Lieb E. In the present paper the estimation obtained in case when there is a different interaction between particles.